Entrepreneurial Orientation and Financial Capability: A Study of Tourism MSMEs in Labuan Bajo - Rukmiyati Ni Made Sri; Suastini Ni Made; Putu Wita Indrayani I Gusti Ayu; Pitanatri Ni Made Uttari; Hardina; Kartini Luh Putu (SHS Web of Conferences, 2025)
Micro, small, and medium enterprises (MSMEs) play a pivotal role in driving economic development by creating jobs, promoting exports, and enhancing national revenue. The Resource-Based View (RBV) theory emphasizes that internal resources, like entrepreneurial orientation (EO), are key to gaining a competitive edge. EO—characterized by innovation, proactivity, and risk-taking—helps MSMEs navigate dynamic market environments. This study examines the entrepreneurial orientation and financial capability of MSMEs in the tourism sector of Labuan Bajo, a region experiencing significant growth due to its popularity as a tourist destination. The research finds no notable differences in EO or financial capability based on gender, age, or educational background among MSME owners. However, business duration strongly influences both entrepreneurial orientation and financial capability, with more experienced owners exhibiting stronger capabilities. These findings suggest that practical, experience-based learning and inclusive training programs are essential for fostering MSME success. Government initiatives aimed at providing better financial support, especially for women-led MSMEs, are also recommended to enhance inclusivity and promote sustainable business growth. The study’s focus on Labuan Bajo limits the generalizability of its findings, indicating the need for further research across different regions and sectors.